(untitled) (AL JAMI: Jurnal Ilmiah Keagamaan, Pendidikan dan Dakwah, 2025)
This study examines the challenges of developing the religious potential of school-age children amidst modernization and the role of community organizations such as Karang Taruna. The main objective is to investigate the role of Karang Taruna Akasia Kreatif in developing the religious potential of school-age children and to identify supporting and inhibiting factors on Jalan Akasia, Banjarbaru. Using a descriptive qualitative approach, this field research involved observation, in-depth interviews with the Head of RT. 05, the Head of Karang Taruna Akasia Kreatif, and 10 school-age children, as well as documentation. Data analysis includes reduction, presentation, and verification. The findings indicate that Karang Taruna Akasia Kreatif actively develops children's religious potential through structured religious programs, which increase participation and skills (eg, Azan, Habsyi, Tilawah). Supporting factors include high member participation and strong support from the community and government. Meanwhile, inhibiting factors come from internal organizations (lack of systematic knowledge among some members, busy schedules) and external factors (inadequate facilities)